Western civilization and the Far East - King-Hall, Stephen (Methuen, 1924)
This book introduce a general survey. The beginning of China's labour. Western civilization and the Far East. Synthetic manufacture of a great power called Japan. China in travail. The domestic politics of Japan. Japanese policy in China since 1911...